Efficient and controllable photoluminescence in novel solid solution Ca1−xSrxHf4(PO4)6:Eu2+ phosphors with high thermal stability for white light emitting diodes. Issue 31 (24th July 2018) - Xin, Shuangyu; Gao, Miao; Wang, Chuang; Wang, Xuejiao; Zhu, Ge; Zhou, Faguang; Li, Zhuowei; Wang, Yuhua
Abstract : The tunable photoluminescence properties of (Ca, Sr)Hf4 (PO4 )6 :Eu 2+ solid solution phosphors with high thermal stability and quantum efficiency were investigated. Abstract : To explore a new family of phosphate phosphors for application in ultraviolet-based light emitting diodes (LEDs), novel promising blue emission solid solution phosphors, Ca1− x Sr x Hf4 (PO4 )6 :Eu 2+, with efficient and controllable photoluminescence were synthesized and characterized in the full range of 0 ≤ x ≤ 1. To deeply understand the relationship between the structure and properties of the phosphors, the phase purities, crystal structures and linear structural evolutions of Ca1− x Sr x Hf4 (PO4 )6 :Eu 2+ solid solutions were investigated in detail by FT-IR spectroscopy and Rietveld structure refinement of their powder XRD patterns and verified by high transmission electron microscopy (HRTEM). The linear structural evolutions induced controllable blue emission with high quantum efficiency and excellent thermal stability in the Ca1− x Sr x Hf4 (PO4 )6 :Eu 2+ solid-solution phosphors. Moreover, the photoluminescence properties in Ca1− x Sr x Hf4 (PO4 )6 :Eu 2+ can be optimized by adjusting the components. The mechanism of the controllable luminescence properties was also investigated in detail. Excellent thermal stability was obtained in Ca1− x Sr x Hf4 (PO4 )6 :Eu 2+, and the thermal quenching mechanism was investigated. Finally, white LEDs were fabricated and their electroluminescence properties were investigated. This simple and effective method to optimize the photoluminescence properties of phosphors can be used for designing other novel solid-solution phosphors.